Krajobraz poruszony - Krajewska, Anna (Przestrzenie Teorii, 2025)
The editorial in the issue, Landscape as a Way of Experiencing the World – Theories, Aesthetics, Practices (Part 1), serves to present diverse research perspectives, whose common starting point is reflection primarily on action in various fields of experience. Landscapes, viewed as experiencing the world, exist in spaces in theory, art practices and aesthetics.